Colombia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2019)
This Selected Issues paper examines the impact of the Financing Law on both tax revenues and the economy. This paper assesses the main tax measures introduced by the law and their dynamic impact on tax revenue through macroeconomic transmission channels. Despite various reforms in recent years, non-oil tax revenues in Colombia remain comparatively low. The Financing Law should raise tax revenues in 2019 but will likely create shortfalls thereafter. The model-based simulations point to sizeable increases in private investment. The simulations suggest that the Law could boost medium-term growth by around 0.2 percent of GDP but will reduce tax revenues by over 1/2 percent of GDP in the medium term. The key channel is through a lower corporate burden through lower corporate income tax and allowing input credit for value added tax on capital goods. The analysis finds that the Law may boost medium-term growth by around 0.2 percent of GDP, but it may lead to future tax revenue shortfalls starting in 2020.